The application of data envelopment analysis and queuing models to large scale computer networks - Najmeh, Malekmohammadi; Zainuddin, Hishamuddin (Science and Research Branch, 2010)
This paper considers a technique for evaluating the operational efficiency of large-scale computer networks via data envelopment analysis and queuing models. The technique consists of two stages. In the second stage, a target DEA model is used which yield the advantages of the proposed technique over the previous one. Numerical illustration is provided to show the improvement of our aspect.